2015
DOI: 10.1111/jnc.13279
|View full text |Cite
|
Sign up to set email alerts
|

Maturational alterations in constitutive activity of medial prefrontal cortex kappa‐opioid receptors in Wistar rats

Abstract: Opioid receptors can display spontaneous agonist-independent G-protein signaling (basal signaling/constitutive activity). While constitutive κ-opioid receptor (KOR) activity has been documented in vitro, it is unknown if KORs are constitutively active in native systems. Using [35S] GTPγS coupling assay that measures receptor functional state, we identified the presence of medial prefrontal cortex (mPFC) KOR constitutive activity in young rats that declined with age. Furthermore, basal signaling showed an age-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
(117 reference statements)
1
13
0
Order By: Relevance
“…In this study, our data support the latter mechanism: a single exposure to an acute stressor causes a lasting constitutive activation of VTA κORs that suppresses plasticity at inhibitory synapses correlated with stress-induced drug-seeking (Figure 7). While previous studies have demonstrated constitutive activity of κORs in cultured cells and in the rat brain (Wang et al, 2007; Sirohi and Walker, 2015), ours is the first demonstration of experience-induced changes in constitutive activity of these receptors. This represents a novel mechanism of regulation by acute stress of the dynorphin-κOR system, and sheds new light on signaling pathways involved in reinstatement of drug seeking.
10.7554/eLife.23785.011Figure 7.Constitutive activation of κORs by stress.( A ) During stress, dynorphin binding to the κOR triggers a shift to a constitutively active state.
…”
Section: Discussionmentioning
confidence: 42%
“…In this study, our data support the latter mechanism: a single exposure to an acute stressor causes a lasting constitutive activation of VTA κORs that suppresses plasticity at inhibitory synapses correlated with stress-induced drug-seeking (Figure 7). While previous studies have demonstrated constitutive activity of κORs in cultured cells and in the rat brain (Wang et al, 2007; Sirohi and Walker, 2015), ours is the first demonstration of experience-induced changes in constitutive activity of these receptors. This represents a novel mechanism of regulation by acute stress of the dynorphin-κOR system, and sheds new light on signaling pathways involved in reinstatement of drug seeking.
10.7554/eLife.23785.011Figure 7.Constitutive activation of κORs by stress.( A ) During stress, dynorphin binding to the κOR triggers a shift to a constitutively active state.
…”
Section: Discussionmentioning
confidence: 42%
“…The release of DYN opioid peptides and KOR activation putatively regulate acute elevations in N 2 O-induced mesolimbic dopamine release [31] . Although, maturational decline in KOR constitutive activity occurs in rats [32] , which could differentially affect KORs ligand efficacy and impart consequential age-related effects. Age-dependent decline in KOR activity or its desensitization likely explain the N 2 O-induced, DYN-mediated activation of the nonopioid targets responsible for amyloidogenesis, including modulation of glutamate receptors [33] and caspase activation.…”
Section: Environmental Nitrous Oxide (N 2 O) Exposmentioning
confidence: 99%
“…Given that Agostini et al report non-significant differences in humoral immunity among aMCI converters versus non-converters yet a higher avidity index (which could be indicative not necessarily of robust host immune response, but of greater accumulation of viral antigen and, thereby, more favorable geometric interaction with antibody, as avidity is determined by antigen-antibody complexing), alternative explanations beyond robust host immunity must be considered in the link between HSV-1 reactivation and AD. 2 It is hypothesized here that chronic, trace N 2 O-induced DYN release promotes HSV-1 reactivation through specific immunosuppression, whereas high viral load (indicative of higher avidity) depletes N 2 O-induced, DYN-mediated non-opioid reactivity (presumably enhanced due to the age-related decline in the activity of cognate receptors 12 ), and this protects against DYN neurotoxicity and conversion to widespread neurodegeneration among aMCI. It is also interesting to speculate whether HSV reactivation in AD occurs proportionately to the maturational decline in the constitutive activity of KOR, which could differentially affect KOR ligand efficacy and impart consequential nonopioid, AD-related effects (i.e.…”
Section: Environmental Nitrous Oxide Exposure Ad Pathology and Hsv-1mentioning
confidence: 99%
“…This model of N 2 O-induced neurodegeneration is likely to be more pronounced in the aged cohort due to the constitutive decline in the activity of cognate KOR receptors for DYN peptide that has been shown in the Wistar rat, compounding the non-opioid action of DYN. 12 The Wistar rat has also been previously shown to have particular susceptibility to the chronic effects of N 2 O, including "shrinkage and vacuolation of neurons in cerebral cortex." 15…”
Section: Animal Models To Test Trace N 2 O-induced Hsv Reactivationmentioning
confidence: 99%